Breaking news - Michaels, Fern. (New York : Kensington Pub. Corp., 2012)
Teresa "Toots" Amelia Loudenberry is extending her stay in Charleston to help care for her ailing housekeeper, Bernice. Here in her beloved hometown, the air is rich with the scent of azaleas and honeysuckle and there's always a pitcher of sweet tea (or something a little stronger) close to hand. Not that the ladies have much time for relaxing. Ida's new line of cosmetics, "Seasoned," is about to launch, and Toots, Mavis, and Sophia are relishing their new careers as models. Most exciting of all, Toots's daughter, Abby, is getting married. Toots has her hands full, especially when Abby's criminal ex-boss resurfaces and the bride-to-be jeopardizes her big day in order to catch him. Toots is so busy taking care of the upcoming nuptials that she's blindsided by her own unexpected romance. After eight husbands, she's sworn never to get involved again. But every godmother, fairy or otherwise, loves a story that ends with happily-ever-after...
Keywords: Friendship -- Fiction; Cosmetics -- Fiction; Models (Persons) -- Fiction; Weddings -- Fiction; Supervisors -- Fiction; Man-woman relationships -- Fiction; Female friendship -- Fiction; Mothers and daughters -- Fiction; Domestic fiction; Rich people -- Fiction; Charleston (S.C.) -- 21st century -- Fiction; South Carolina -- Fiction; Love stories